Exploring the History of Tourism in Ancient and Medieval Nepal: A Study of Visitors and their Activities - Kafle, Dol Raj (KMC Journal, 2023)
Nepal is the place of tourist attraction and destination since the ancient time. Taking this into consideration using historical design of qualitative research, this study examines the visitors who came to the country during the ancient and medieval periods from the perspective of tourism in Nepal. The study explores the reasons for travel to Nepal, such as for pilgrimages, diplomatic missions, as refugees, and discusses the activities that these visitors were involved in during their time in the country. The study used secondary sources, including travelogues and historical memoirs, to draw conclusions about the development of tourism in Nepal during this time period. The findings suggest that visitors to Nepal during this time can be considered tourists, and their activities were similar to those of modern tourism.